Study on the wall-breaking method of carotenoids producing yeast Sporidiobolus pararoseus and the antioxidant effect of four carotenoids on SK-HEP-1 cells. Issue 8 (14th September 2019) - Liu, Chang; Cheng, Yuliang; Du, Chao; Lv, Tianqi; Guo, Yahui; Han, Mei; Pi, Fuwei; Zhang, Weiguo; Qian, He
Abstract: The cell wall of carotenoids producing yeast Sporidiobolus pararoseus was broken through five different methods: acid-heating method, dimethyl sulfoxide (DMSO) method, enzymatic method, high-pressure homogenization (HPH) method, and cell autolysis method. HPH method not only brought the optimum breaking effect (wall-breaking extent of 72.3%) and the highest carotenoid extraction rate (67.2%), but also had the advantages of short-time, simple process, safe, and pollution-free. After optimization, the wall-breaking extent and the carotenoid extraction rate were enhanced to 78.3% and 82.5%, respectively. And the optimum conditions of HPH were obtained as homogenization pressure 80 MPa, bacterial liquid concentration 8% and homogenization for three times. Moreover, cell experiments demonstrated that all of the four carotenoids (β-carotene, γ-carotene, torulene, and torularhodin) purified from intracellular products of S. pararoseus. had the effect of resistance to oxidative damage from hydrogen peroxide on SK-HEP-1 cells, and torulene showed the most notable effect among them. Graphical Abstract: